THE USE OF FIREARMS AGAINST A CONVICT IN CASE OF AN ESCAPE - Milić, Ivan; Drakić, Dragiša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The use of firearms is the most severe means of coercion that may be employed against a convict. The legal acts regulating the execution of criminal sanctions also foresee the use of firearms as means of coercion. The authors’ attention is the use of firearms against a convict in the case of escape from a penitentiary. The authors highlight, first and foremost, who and under what conditions may employ a firearm against a convict. The relevant legal acts are analyzed and adequate and deficient solutions concerning the use of firearms are identified. The authors suggest de lege ferenda solutions.
Keywords: convict, escape, firearm, penitentiary.